Characterization of mechanical properties by preferential supplant of cement with GGBS and silica fume in concrete. (2021) - Mohan, A.; Tabish Hayat, Md
Abstract: An attempt is made to replace an ordinary Portland cement by a mineral admixture such as ground granulated blast furnace slag (GGBS) and silica fume in concrete mixes. The research practice is done to find an alternative that could be used as areplacement for cement, which is more reliable for sustainable development and the lowest possible environmental consequences. The research is done by preferential supplant of cement with GGBS and silica fume without using any admixtures for the concrete grade-M30 with varying ground granulated blast furnace slag i.e., 40%, 50%, 60% and 10% of silica fume added on itto accelerate the pozzolanic effect as a preferential supplant of cement in concrete. Mechanical properties such as compression, tension, split tensile, and flexural strength test is performed to know the suitable scope of the concrete based on their effectiveness and the amount of cement could be supplanted with ground granulated blast furnace slag and silica fume and also to know the most suitable mechanical properties. Stress–strain behaviors for different mix proportions are comparatively studied and flexural strength of reinforced beams is tested.